Economies of design - Julier, Guy, ....- (Los Angeles : SAGE, 2017)
This ground-breaking book shines a spotlight on how design has become embedded in political economies, emerging as a vital feature of neoliberal economic systems, from urban strategies to commercial processes to government policy-making.
Keywords: Design -- Economic aspects